Pathomorphological parameters of sepsis-associated encephalopathy in deceased septic patients without purulent lesions to the brain - T. V. Shulyatnikova; L. M. Tumanska (Сучасні медичні технології, 2024)
Sepsis-associated encephalopathy (SAE) clinically manifests by delirium and decreased consciousness less than 15 points on Glasgow Coma Scale. SAE pathophysiology includes neuroinflammation, ischemic-hypoxic and dysmetabolic mechanisms. Despite the high frequency and the important role in thanatogenesis, pathomorphological criteria of SAE remain to be defined.